Enhanced antibody production of human-human hybridomas by retinoic acid - Inoue, Yuichi (Kluwer Academic Publishers, 2000)
The enhancement of human monoclonal antibody production by retinoic acid (RA) was evaluated usingthe human-human hybridoma cell line BD9 underserum-free culture condition. The amount of humanIgG secreted by BD9 hybriodmas was enhanced abouteight-fold by treatment with 10(-7) M of RA for 4days. Northern blot analysis showed that both mRNAlevels of the IgG light and heavy chains were markedlyincreased by RA when compared with control without RAtreatment. On the other hand, it was found thatcontinuous treatment of cells with RA was not alwaysrequired to exhibit the enhancing effect, suggestingthat RA may act as a trigger for IgG gene expression. The comparison between extra- and intracellular IgGamounts by immunoblot analysis suggests that thesecretion rate of IgG may be accelerated by RAtreatment. These results suggest that RA may be aneffective culture additive for efficient production ofhuman monoclonal antibody using human-humanhybridomas.